Georgia : Financial System Stability Assessment. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2014)
This paper discusses findings of the Financial System Stability Assessment for Georgia. Georgia has weathered several shocks, but still faces a number of important risks. The economy has withstood well the conflict with Russia, the global financial crisis, and domestic political uncertainty. Significant steps have been taken to strengthen banking regulation and supervision, which exhibit a very high degree of compliance with international standards. The National Bank of Georgia has also introduced an advanced risk-based supervisory regime while maintaining a conservative approach aimed at detecting vulnerabilities at an early stage, and allocating supervisory resources in the most efficient and effective manner.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet